Noninvasive assessment of volume status in patients with end-stage kidney disease using a wearable monitor and cutaneous hydration sensor - Melissa C. Caughey; Dhatri Kakarla; Sora Lee; Simran K. Singh; Caroline J. Poulton; Emily H. Chang (BMC Nephrology)
Abstract Background Fluid volume overload is a frequent cause of hospitalization for patients with end-stage kidney disease (ESKD), and disproportionately occurs during the 2-day hemodialysis gap when patients are most susceptible to poor volume control. Noninvasive, wearable devices may hold potential for at-home volume status monitoring to prevent hospitalization but clinical validation in ESKD populations is limited. Methods A total of 17 study participants (41% female, 76% Black, median age = 68 years) were recruited for in-center testing of hydration status pre- and post-hemodialysis. Percent lung water (%LW) and skin hydration were noninvasively assessed and compared with established clinical and hemodynamic and markers of hydration status. Results Median within-subject change in systolic blood pressure (-10 mmHg, p = 0.08), diastolic blood pressure (-6 mmHg, p = 0.06), weight (-1.6 kg, p < 0.0001), heart rate (-10 bpm, p = 0.09), and %LW (-1.0%, p = 0.03) declined from pre- to post-dialysis. When analyzed as a continuous measurement, %LW was not correlated with systolic blood pressure, weight, heart rate, or dyspnea score. Skin hydration demonstrated poor correlation with %LW, but statistically differed (42 vs. 23 a.u.; P = 0.03) when stratified by the broader categories of borderline-high/elevated versus normal %LW, suggesting an ability to detect abnormal fluid status. Conclusion In this small pilot study, noninvasive assessment of %LW was sufficiently sensitive to detect pre-to-post hemodialysis change in fluid status. These results support future evaluations in larger studies of patients with ESKD. Noninvasive, wearable devices may be a feasible strategy to assess volume status in the ESKD population, an approach which could potentially be extended to at-home settings.